MAP7 and MUCL1 Are Biomarkers of Vitamin D3-Induced Tolerogenic Dendritic Cells in Multiple Sclerosis Patients - Navarro-Barriuso, Juan; Mansilla, María José; Quirant-Sánchez, Bibiana; Ardiaca-Martínez, Alicia; Teniente-Serra, Aina; Presas-Rodríguez, Silvia; ten Brinke, Anja; Ramo-Tello, Cristina; Martínez-Cáceres, Eva M. (Frontiers in Immunology, 2019)
The administration of autologous tolerogenic dendritic cells (tolDC) has become a promising alternative for the treatment of autoimmune diseases, such as multiple sclerosis (MS). Specifically, the use of vitamin D3 for the generation of tolDC (vitD3 tolDC) constitutes one of the most widely studied approaches, as it has evidenced significant immune regulatory properties, both in vitro and in vivo. In this article, we generated human vitD3 tolDC from monocytes from healthy donors and MS patients, characterized in both cases by a semi-mature phenotype, secretion of IL 10 and inhibition of allogeneic lymphocyte proliferation. Additionally, we studied their transcriptomic profile and selected a number of differentially expressed genes compared to control mature and immature dendritic cells for their analysis. Among them, qPCR results validated CYP24A1, MAP7 and MUCL1 genes as biomarkers of vitD3 tolDC in both healthy donors and MS patients. Furthermore, we constructed a network of protein interactions based on the literature, which manifested that MAP7 and MUCL1 genes are both closely connected between them and involved in immune-related functions. In conclusion, this study evidences that MAP7 and MUCL1 constitute robust and potentially functional biomarkers of the generation of vitD3 tolDC, opening the window for their use as quality controls in clinical trials for MS.